Psychological assessment of the attitude to oral diseases of patients of older age groups who have applied for dental care - A. A. Alekseeva; G. I. Lukina; I. S. Glatkov; A. V. Lukin (Эндодонтия Today)
Aim. Determination of the psychological type of attitude to the patient's illness, depending on gender and age group, which will further improve communication between the patient and the dentist.Materials and methods. This article provides a psychological assessment of patients in relation to diseases of the oral cavity at a dental appointment using the adapted TOBOL technique. This technique is based on typing patients according to certain cognitive characteristics described in the article. For this study, 65 people of older age groups were interviewed.Results. The frst group of attitudes towards the disease included 27 patients (41.5%), the second – 24 (37%), the third – 14 (21.5%). 11 (45.8%) men were assigned to the frst group, 8 (33.3%) men – to the second and 5 (20.9%) – to the third group. Women showed a distribution: 16 (39%) women belonged to the frst group, 16 (39%) – to the second and 9 (22%) – to the third group, respectively. Negative attitude towards dental diseases, reluctance to treat them sharply increases in centenarians.Conclusions. With increasing age, there is a growing tendency towards pessimization and aggression. Sensitized attitudes toward illness, depression, refusal of treatment, or blame-shifting complicate diagnosis and subsequent treatment. To prevent unwanted emotions and improve the quality of communication, the dentist should be guided by an individual approach to these patients, which should be based on the basic principles of ethics and deontology. Only then will dental treatment be effective and complete.